2017
DOI: 10.1002/jmr.2675
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics investigation of stereoselective inhibition mechanism of HIF‐2α/ARNT heterodimer

Abstract: Hypoxia-inducible factors (HIFs) are heterodimeric transcription factors related with the onset and progression of solid tumors. Studies demonstrated a class of tetrazole containing chiral inhibitors could stereoselectively disrupt the HIF-2 dimerization and reduce the target gene expression. However, the dynamical features and structural motifs of the HIF-2 heterodimer caused by the binding of enantiomers have not been rationalized at the atomistic level. In this work, molecular dynamics (MD) simulations comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The lessened contacts of interdomain forcefully indicate that some crucial interactions between HIF‐2α and ARNT are disrupted as binding of 2 inhibitors. Our previous study has shown that the apo 1 was stabilized by the foremost H‐bond and salt bridge interactions (Asp240‐Arg366 and Arg247‐Glu362) as well as the assistant H‐bonds (Tyr327‐Arg440 and Glu320‐Tyr450) located on the β‐sheets of binding interface. When the PT2399 and 0X3 bind into the HIF‐2α domain, these foremost H‐bond and salt bridge interactions (Asp240‐Arg366 and Arg247‐Glu362) are largely disrupted, and the assistant H‐bonds (Tyr327‐Arg440 and Glu320‐Tyr450) are still retained (Figure D‐F, Table , and Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…The lessened contacts of interdomain forcefully indicate that some crucial interactions between HIF‐2α and ARNT are disrupted as binding of 2 inhibitors. Our previous study has shown that the apo 1 was stabilized by the foremost H‐bond and salt bridge interactions (Asp240‐Arg366 and Arg247‐Glu362) as well as the assistant H‐bonds (Tyr327‐Arg440 and Glu320‐Tyr450) located on the β‐sheets of binding interface. When the PT2399 and 0X3 bind into the HIF‐2α domain, these foremost H‐bond and salt bridge interactions (Asp240‐Arg366 and Arg247‐Glu362) are largely disrupted, and the assistant H‐bonds (Tyr327‐Arg440 and Glu320‐Tyr450) are still retained (Figure D‐F, Table , and Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…As many applications of the external force involve the restructuring of the target system, the solvent box is often large and exacerbates the cost of the sampling. Beyond our group, ASMD has been used successfully to obtain the energetics of several challenging systems, including the characterization of a host–guest interaction, , mechanism of the complex dynamics, mutagenesis, binding affinity, protein–ligand interactions, and protonation effects …”
Section: Introductionmentioning
confidence: 99%